Barriers to Thai Doctoral Music Students’Socialisation - Saibunmi, Skowrung; Trakarnrung, Somchai (Malaysian Journal of Music, 2016)
A doctoral music degree is a new degree in Thailand. Although the first PhD programme in music was established in 2005, there are only four universities that provide doctoral programmes in music in 2016. However, there are a couple of universities that plan to launch doctoral music programmes in the near future. If the number of doctoral programmes in music and the number of graduates has started to grow, it is important to consider the barriers to doctoral music student socialisation because they relate to the completion of the degree. This paper aims to investigate barriers that Thai doctoral music students encounter in doctoral socialisation. This leads to the main question: What are the barriers that Thai doctoral music students encounter in doctoral socialisation? The key instrument used for this research was in-depth interviews with 12 doctoral students and graduates during four different stages of doctoral education across four Thai universities that have launched PhD programmes in music. The results indicated that barriers to Thai doctoral music student socialisation emerge from three segments: 1) student-related barriers (backgrounds, predispositions, investment, personal communities, self-concept and psychological issues); 2) barriers of integrating into the doctoral programme (learning, peer climate, relationships with faculty and friends and dissertation phases); and 3) institutional barriers (admissions, academic programme curriculums and requirements).